INCREASING STUDENT LEARNING OUTCOMES IN NEGOTIATION TEXT MATERIALS THROUGH IRC MODEL C IMPLEMENTATION IN CLASS X TB 3 SMK NEGERI 1 DLANGGU - Ervina Routine Styarini (Sean Institute, 2022)
This type of research is a class action research (CAR) which aims to (1) determine the increase in student achievement of class X TB 3 SMK Negeri 1 Dlanggu Mojokerto Regency regarding negotiating text by applying the CIRC model, (2) knowing student responses after the CIRC model was applied to learning Indonesian for class X TB 3 SMK Negeri 1 Dlanggu Mojokerto Regency about negotiating text. The research was conducted from January to February 20 20 with 34 students in class X TB 3 at SMK Negeri 1 Dlanggu as subjects . The research phase includes cyclical activities with each cycle consisting of the stages of planning, implementing, observing, and reflecting. The results showed that (1) learning with the CIRC model had a positive impact on improving student achievement which was marked by an increase in student mastery in each cycle, namely cycle I (72.73%) and cycle II (87.88%). In the activity aspect the students also showed remaining active in learning and in the implementation aspect of the RPP it showed that learning was in the good category, namely in the first cycle it received an average score of 3.3 (good) and increased to 3.5 (good) in the second cycle and implementation reached 100%, ( 2) the application of the CIRC model has a positive influence, namely it can increase student learning motivation as indicated by the average student answers which state that students are interested and interested in the CIRC model so that they become motivated to learn.